Gender disparities in fear of failure among 15‐year‐old students: The role of gender inequality, the organisation of schooling and economic conditions. (7th December 2020) - Borgonovi, Francesca; Han, Seong Won
ABSTRACT: Introduction: Prior research indicates that female students express higher fear of failure than male students and that fear of failure is associated with lower social and emotional well‐being and higher levels of stress, anxiety, burnout and depression. Fear of failure also leads individuals to limit their choices and take fewer risks than would be warranted given their ability and context to minimise the possibility of failing. Methods: We examined cross‐country differences in gender gaps in fear of failure as well as factors that explain gender gaps and variations of gender gaps across countries using multilevel modelling techniques. Participants were 517, 047 15‐year‐old students from 59 countries who took part in the 2018 Programme for International Student Assessment (PISA). Results: Within countries, students with higher reading achievement and who lacked a growth mindset reported higher fear of failure. The gender gap in fear of failure was especially high among high‐achieving students and students with high‐achieving peers. The size of the gender gap in fear of failure differed across countries: it was higher in countries with higher levels of economic prosperity, with lower levels of societal‐level gender inequality and countries with comprehensive education systems. Conclusions: The greater prevalence of fear of failure among female students among high‐achieving students attending high‐achieving schools in prosperous and more gender equal societies could help to explain the paradox of the persistent underrepresentation of females in certain occupations in contexts that are most supportive of females. Highlights: We analysed fear of failure among 517, 047 15‐year‐old students from 59 countries. Female 15‐year‐old students express higher fear of failure than male students. The gender gap in fear of failure is higher among high‐achievers. The gender gap in fear of failure is higher in high‐achieving schools. In prosperous and more gender equal counties the gender gap in fear of failure is highest.